Altering the effectiveness of radical traps in atom transfer radical coupling reactions of polymer chains. (3rd October 2017) - Wu, Jessica P.; Pan, Ching W.; Heiler, Katherine E.; Ching, Megan E.; Tillman, Eric S.
Abstract: Atom transfer radical coupling (ATRC) reactions assisted by radical traps were studied under various conditions, with the extent of coupling of polymer chains monitored as a function of time. When using a radical trap that tended to aggregate into dimers, such as 2-methyl-2-nitrosopropane (MNP), the rate of coupling was enhanced when conditions were adjusted to favor its de-aggregation to the monomeric form: less polar solvent mixtures and/or the addition of β-cyclodextrin (β-CD). With radical traps that did not aggregate, such as nitrosobenzene (NBz) and N - tert -Butyl-α-phenylnitrone (tBuPN), coupling was generally accelerated under conditions consistent with higher KATRP values. MALDI-TOF analysis was used to confirm the incorporation of the radical trap into the polymer dimers, supporting the mechanistic pathway proposed for radical trap-assisted ATRC. The effect of aggregation of the radical trap was further probed by using fractional equivalents of NBz in the coupling reaction, with a full equivalent leading to end-capped polymer chains that were unable to dimerize. By reducing the equivalents of NBz, the extent of coupling could be controlled by the temperature, with higher temperatures (80 °C) allowing ATRC to compete with RTA-ATRC and higher extents of coupling were observed. Graphical abstract: Highlights: The trapping ability of the 2-methyl-2-nitrosopropane (MNP) is sensitive to both solvent conditions and the inclusion of β-cyclodextrin. Nitrosobenzene (NBz) leads to end-capping of the polymer chains, transforming the C-Br functionality into nitroxide functionality. Coupling reactions performed at 80 °C result in dimerized products formed by competition between RTA-ATRC and ATRC when nitrosobenzene is used as the radical trap.